Fish oil replacement with different vegetable oils in Murray cod : evidence of an 'omega-3 sparing effect' by other dietary fatty acids - Giovanni Turchini; David Francis; Shyamalie Sendadheera; Thanongsak Thanuthong; S De Silva (2011)
Fish oil replacement with different vegetable oils in Murray cod : evidence of an 'omega-3 sparing effect' by other dietary fatty acids